Polyglycolic acid catalyst and preparation method thereof

By using amino acids and zinc acetate catalysts in the ring-opening polymerization of glycolide, the problems of solvent residues and heavy metal contamination are solved, and efficient and pure polyglycolic acid catalysts are realized. They are suitable for medical and food fields and meet safe and green applications. need.

CN119320490APending Publication Date: 2025-01-17PETROCHINA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310872001.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The catalysts used in the ring-opening polymerization of glycolides have problems with solvent residues and heavy metal contamination, which affect product purity and safety, and are particularly challenging in applications in the medical and food fields.

Method used

The polyglycolic acid catalyst obtained is free of solvent and metal ion residue by heating and stirring in an oil bath, and has good biocompatibility and safety, and is suitable for medical and food fields.

Benefits of technology

It realizes efficient catalytic ring-opening polymerization of glycolide, shortens the reaction time, improves the monomer conversion rate, and the obtained polyglycolic acid products are purer, suitable for high-end medical and food fields, and are safe and green.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004341328150000071
    Figure BDA0004341328150000071
  • Figure BDA0004341328150000081
    Figure BDA0004341328150000081
  • Figure HDA0004341328160000011
    Figure HDA0004341328160000011
Patent Text Reader

Abstract

The invention discloses a polyglycolic acid catalyst and a preparation method thereof, and the preparation method comprises the following steps: dissolving amino acid and zinc acetate in a solvent, then heating in an oil bath, stirring and refluxing, reacting, after the reaction is finished, washing a product with a solution, and drying to obtain the polyglycolic acid catalyst. The polyglycolic acid catalyst prepared by the preparation method disclosed by the invention has the advantages of good biocompatibility, safety, greenness, no toxicity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical product preparation, and relates to a polyglycolic acid catalyst and a preparation method thereof, and particularly to a safe, green and non-toxic polyglycolic acid catalyst and a preparation method thereof. Background Art

[0002] The ring-opening polymerization of glycolide (GA) requires catalysts to promote the relative molecular mass. In recent years, new catalysts for the ring-opening polymerization of lactones such as glycolide have emerged continuously. Different catalyst systems have different reaction mechanisms for the ring-opening polymerization of lactones. Amino acids, as the basic structural units of proteins in organisms, have attracted great interest with their unique biocompatibility and complete bioabsorbability. In recent years, commercially available amino acid skin care products and nutritional supplements can be seen everywhere. Amino acid molecules have amino and carboxyl functional groups, so they are also good ligands in chemical reactions. Zinc is an essential trace element for the human body. Amino acid zinc obtained by the coordination reaction of amino acids and zinc is a commonly used zinc supplement and nutritional enhancer in medicine and food. Amino acid zinc has great application potential as a green and friendly new depolymerization catalyst that can be applied to glycolide synthesis.

[0003] Chinese patent CN111647144A discloses a method for adjusting the molecular chain structure of polyglycolic acid, wherein glycolide, initiator, lactide, hydroxylated (amide) monomer or hydroxylated polymer or comonomer, and catalyst are sequentially added to a reactor under the protection of normal temperature, normal pressure and inert gas, and polymerization reaction is carried out by heating and stirring. After the reaction is completed, the product is post-processed and dried to obtain polyglycolic acid with adjusted molecular chain structure. The molecular structure is changed by adding some functional groups (hydrophilic and hydrophobic groups -OH, -COOR, etc.) or chain segments (branching, copolymerization, etc.) with special performance characteristics, so as to change the original molecular properties (molecular weight, viscosity, melt index, hydrolysis, crystallinity, processing performance, etc.) of polyglycolic acid; however, the catalyst used in the technology is Sn, Mg, Al, Ca, Fe, Mn metal salts, preferably Sn metal salts, containing heavy metals.

[0004] Chinese patent CN112831031A discloses a method for preparing polyglycolic acid, wherein glycolic acid monomer and / or glycolate monomer are polycondensed to obtain a material with a molecular weight of Mw; the material with a molecular weight of Mw is mixed with polyglycolic acid with a molecular weight of Mw' to react to obtain a material with a molecular weight of Mw. 1 Material; molecular weight Mw 1 Polyglycolic acid is obtained by polymerizing the materials. However, the catalyst of this technology uses stannous octoate and stannous chloride, which has the problem of metal residue.

[0005] Chinese patent CN112280021A discloses a method for preparing polyglycolic acid, which uses glycolic acid as a raw material, heats and distills under the action of xylene until no water is produced; then dioctyl terephthalate is added, and a catalyst and an activator are added at the same time, and the temperature is raised and the pressure is reduced to obtain a polyglycolic acid product. However, this technology is carried out by adding a solvent during the reaction, which is not easy to remove, and a small amount of solvent will remain in the polyglycolic acid product, affecting the purity of the product. Summary of the invention

[0006] The purpose of the present invention is to provide a polyglycolic acid catalyst and a preparation method thereof. The polyglycolic acid catalyst prepared by the present invention is an amino acid catalyst that is well compatible with the human body. The polyglycolic acid catalyst can effectively catalyze the ring-opening polymerization of glycolide during the reaction, and no solvent or metal ions are introduced during the reaction. The obtained polyglycolic acid product is purer and more suitable for use in the medical field.

[0007] To achieve the above object, the present invention provides a method for preparing a polyglycolic acid catalyst, which comprises the following steps: dissolving an amino acid and zinc acetate in a solvent, then heating, stirring, refluxing, and reacting in an oil bath, and after the reaction is completed, washing the product with a solution and drying it to obtain a polyglycolic acid catalyst.

[0008] In the method for preparing the polyglycolic acid catalyst of the present invention, preferably, the molar ratio of the amino acid to zinc acetate is 1:0.5-2.

[0009] In the preparation method of the polyglycolic acid catalyst of the present invention, preferably, the amino acid is at least one of L-alanine, D-alanine, DL-alanine, L-phenylalanine, D-phenylalanine, DL-phenylalanine, L-proline, D-proline, DL-proline, L-threonine, D-threonine, DL-threonine, L-glutamic acid, D-glutamic acid, DL-glutamic acid, L-aspartic acid, D-aspartic acid, DL-aspartic acid, L-isoleucine, D-isoleucine, DL-isoleucine, L-leucine, D-leucine, DL-leucine, L-serine, D-serine, and DL-serine.

[0010] In the method for preparing the polyglycolic acid catalyst of the present invention, preferably, the amino acid is at least one of L-alanine, L-phenylalanine and L-proline.

[0011] In the method for preparing the polyglycolic acid catalyst of the present invention, preferably, the reaction temperature is 40-85° C. and the reaction time is 2-8 hours.

[0012] In the method for preparing the polyglycolic acid catalyst of the present invention, preferably, the reaction temperature is 50-80° C. and the reaction time is 3-6 hours.

[0013] In the method for preparing the polyglycolic acid catalyst of the present invention, preferably, the solvent is at least one of methanol, lauryl alcohol, dodecanol, anhydrous toluene and anhydrous ethyl acetate.

[0014] In the method for preparing the polyglycolic acid catalyst of the present invention, preferably, the method of washing with a solution is to repeatedly use ethanol and water as solvents for washing.

[0015] The present invention also provides a polyglycolic acid catalyst obtained by the preparation method.

[0016] The preparation method of the polyglycolic acid catalyst of the present invention uses amino acids and zinc acetate as raw materials, and can synthesize a variety of amino acid zincs with corresponding configurations corresponding to amino acids with different configurations. The polyglycolic acid catalyst of the present invention has the advantages of good biocompatibility, safety, greenness and non-toxicity.

[0017] The polyglycolic acid catalyst obtained by the preparation method of the present invention has high nucleation efficiency, and the metal salt can effectively catalyze the ring-opening polymerization of lactone monomers, can effectively shorten the reaction time, and improve the monomer conversion rate; compared with the traditional stannous octoate, the polyglycolic acid catalyst of the present invention is used as a catalyst for the ring-opening polymerization of glycolide. When it is used in the reaction process of preparing high molecular weight polyglycolic acid, no solvent or metal ions are introduced in the reaction process, and the polyglycolic acid product obtained by catalysis is free of heavy metals, purer, efficient and safe, and is suitable for the fields of food, medical packaging and high-end medical use. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an infrared image of the polyglycolic acid catalyst obtained in Example 6.

[0019] Figure 2 This is the infrared spectrum of the polyglycolic acid obtained in Example 6. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to further understand the present invention, the polyglycolic acid catalyst and the preparation method thereof of the present invention are now described in conjunction with examples.

[0021] Example 1

[0022] D-phenylalanine and zinc acetate were dissolved in methanol at a molar ratio of 2:1, added to a 500 mL three-necked flask, stirred and refluxed in an oil bath set at 60°C, and reacted for 6 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The final polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Repeatedly rinsed with ethanol and water as solvents and dried.

[0023] 0.05 g 1,4-butanediol, 0.02 g amino acid catalyst, 40 g glycolide and 60 mL anhydrous toluene solution were added to a 500 mL three-necked flask, and the flask was evacuated and purified three times with high-purity nitrogen under vacuum conditions. The device was decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 200 ° C, react for 2 hours, and obtain a polyglycolic acid product, which was purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35 ° C for 24 hours.

[0024] Example 2

[0025] D-leucine and zinc acetate were dissolved in lauryl alcohol at a molar ratio of 2:1, and added to a 500 mL three-necked flask at the same time. The mixture was stirred and refluxed in an oil bath set at 70°C for 5 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The resulting polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Ethanol and water were repeatedly used as solvents for rinsing and drying.

[0026] Add 0.05g 1,4-butanediol, 0.03g amino acid catalyst, 40g glycolide and 60mL anhydrous toluene solution into a 500mL three-necked flask, and evacuate and purify it three times with high-purity nitrogen under vacuum conditions. Vacuum the device for 30 minutes and then seal it with nitrogen. Heat in an oil bath at 200°C and react for 1h to obtain a polyglycolic acid product, which is purified using a Soxhlet extractor for 48h and then vacuum dried at 35°C for 24h.

[0027] Example 3

[0028] D-phenylalanine and zinc acetate were dissolved in methanol at a molar ratio of 1:1, added to a 500 mL three-necked flask, stirred and refluxed in an oil bath set at 80°C, and reacted for 4 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The final polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Repeatedly rinsed with ethanol and water as solvents and dried.

[0029] 0.04g of lauryl alcohol, 0.02g of amino acid catalyst, 40g of glycolide and 80mL of anhydrous toluene solution were added to a 500mL three-necked flask, and it was emptied and purified three times with high-purity nitrogen under vacuum conditions. The device was decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 190°C and react for 3 hours to obtain a polyglycolic acid product, which was purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0030] Example 4

[0031] D-leucine and zinc acetate were dissolved in methanol at a molar ratio of 1:0.8, and added to a 500 mL three-necked flask at the same time. The mixture was stirred and refluxed in an oil bath set at 60°C for 3 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The resulting polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. The product was repeatedly rinsed and dried with ethanol and water as solvents.

[0032] 0.4 g dodecanol, 0.04 g amino acid catalyst, 40 g glycolide and 80 mL anhydrous toluene solution were added to a 500 mL three-necked flask, and the solution was evacuated and purified three times using high-purity nitrogen under vacuum conditions. The device was decompressed and evacuated for 30 minutes, and then sealed with nitrogen. The product was heated in an oil bath at 190 ° C and reacted for 4 hours to obtain a polyglycolic acid product, which was purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35 ° C for 24 hours.

[0033] Example 5

[0034] D-phenylalanine and zinc acetate were dissolved in methanol at a molar ratio of 1:1.2, and added to a 500 mL three-necked flask at the same time. The mixture was stirred and refluxed in an oil bath set at 60°C for 4 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The resulting polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Ethanol and water were repeatedly used as solvents for rinsing and drying.

[0035] In a 500mL three-necked flask, add 0.02g 1,4-butanediol, 0.04g dodecanol, 0.2g amino acid catalyst, 40g glycolide and 20mL anhydrous toluene solution, and evacuate and purify it three times with high-purity nitrogen under vacuum conditions. The device is decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 180°C and react for 4 hours to obtain a polyglycolic acid product, which is purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0036] Example 6

[0037] D-leucine and zinc acetate were dissolved in methanol at a molar ratio of 2:1, added to a 500 mL three-necked flask, stirred and refluxed in an oil bath set at 60°C, and reacted for 5 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The final polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Repeatedly rinsed with ethanol and water as solvents and dried.

[0038] In a 500mL three-necked flask, add 0.4g 1,4-butanediol, 0.4g lauryl alcohol, 0.4g amino acid catalyst, 40g glycolide and 80mL anhydrous toluene solution, and evacuate and purify it three times with high-purity nitrogen under vacuum conditions. The device is decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 160°C and react for 3 hours to obtain a polyglycolic acid product, which is purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0039] Example 7

[0040] D-phenylalanine and zinc acetate were dissolved in methanol at a molar ratio of 1:2, and added to a 500 mL three-necked flask at the same time. The mixture was stirred and refluxed in an oil bath set at 70°C for 6 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The resulting polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Ethanol and water were repeatedly used as solvents for rinsing and drying.

[0041] In a 500mL three-necked flask, add 0.02g dodecanol, 0.02g lauryl alcohol, 0.004g amino acid catalyst, 40g glycolide and 80mL anhydrous toluene solution, and evacuate and purify it three times with high-purity nitrogen under vacuum conditions. The device is decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath set at 170°C and react for 4 hours to obtain a polyglycolic acid product, which is purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0042] Example 8

[0043] D-leucine and zinc acetate were dissolved in methanol at a molar ratio of 1:1.5, added to a 500 mL three-necked flask, stirred and refluxed in an oil bath set at 70°C, and reacted for 5 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The final polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Repeatedly rinsed with ethanol and water as solvents and dried.

[0044] In a 500mL three-necked flask, add 0.02g 1,4-butanediol, 0.01g dodecanol, 0.01g lauryl alcohol, 0.02g amino acid catalyst, 40g glycolide and 80mL anhydrous toluene solution, and evacuate and purify it three times with high-purity nitrogen under vacuum conditions. The device is decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 180°C and react for 3 hours to obtain a polyglycolic acid product, which is purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0045] Example 9

[0046] D-phenylalanine and zinc acetate were dissolved in methanol at a molar ratio of 1:1.8, and added to a 500 mL three-necked flask at the same time. The mixture was stirred and refluxed in an oil bath set at 60°C for 5 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The resulting polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Ethanol and water were repeatedly used as solvents for rinsing and drying.

[0047] 0.04 g 1,4-butanediol, 0.02 g amino acid catalyst, 40 g glycolide and 80 mL anhydrous toluene solution were added to a 500 mL three-necked flask, and the flask was evacuated and purified three times with high-purity nitrogen under vacuum conditions. The device was decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 160°C and react for 3 hours to obtain a polyglycolic acid product, which was purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0048] Example 10

[0049] D-leucine and zinc acetate were dissolved in methanol at a molar ratio of 1:2, added to a 500 mL three-necked flask, stirred and refluxed in an oil bath set at 80°C, and reacted for 6 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The final polyglycolic acid catalyst was dried in a vacuum oven at 40°C for 48 hours. Repeatedly rinsed with ethanol and water as solvents and dried.

[0050] 0.04 g 1,4-butanediol, 0.02 g amino acid catalyst, 40 g glycolide and 80 mL anhydrous toluene solution were added to a 500 mL three-necked flask, and the flask was evacuated and purified three times with high-purity nitrogen under vacuum conditions. The device was decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 160°C and react for 4 hours to obtain a polyglycolic acid product, which was purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0051] Comparative Example 1

[0052] The difference from Example 6 is that stannous octoate catalyst is used instead of amino acid catalyst.

[0053] A commercially available stannous octoate catalyst produced by Alfa Aesar (China) Chemical Co., Ltd. was used.

[0054] In a 500mL three-necked flask, add 0.4g 1,4-butanediol, 0.4g lauryl alcohol, 0.4g stannous octoate catalyst, 40g glycolide and 80mL anhydrous toluene solution, and evacuate and purify it three times with high-purity nitrogen under vacuum conditions. The device is decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 160°C and react for 3 hours to obtain a polyglycolic acid product, which is purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0055] Comparative Example 2

[0056] The difference from Example 6 is that D-leucine is replaced by stannous chloride.

[0057] Stannous chloride and zinc acetate were dissolved in methanol at a molar ratio of 2:1, added to a 500 mL three-necked flask, stirred and refluxed in an oil bath set at 60°C, and reacted for 5 hours. After the reaction, the system was cooled to room temperature, filtered, and the product was repeatedly washed with ethanol-water. The final catalyst was dried in a vacuum oven at 40°C for 48 hours. The catalyst was repeatedly rinsed and dried with ethanol and water as solvents to obtain a catalyst.

[0058] 0.4 g 1,4-butanediol, 0.4 g lauryl alcohol, 0.4 g catalyst, 40 g glycolide and 80 mL anhydrous toluene solution were added to a 500 mL three-necked flask, and it was evacuated and purified three times with high-purity nitrogen under vacuum conditions. The device was decompressed and evacuated for 30 minutes, and then sealed with nitrogen. Heat in an oil bath at 160°C and react for 3 hours to obtain a polyglycolic acid product, which was purified using a Soxhlet extractor for 48 hours, and then vacuum dried at 35°C for 24 hours.

[0059] The polyglycolic acid products obtained in the examples and comparative examples were subjected to viscosity analysis. The results are shown in Table 1.

[0060] Table 1 PGA product viscosity

[0061]

[0062]

[0063] It can be seen from the results of Example 6, Comparative Example 1 and Comparative Example 2 that, compared with the prior art, the product prepared using the amino acid catalyst of the present application has a higher viscosity, indicating that the molecular weight of the obtained product is larger and the product purity is higher.

[0064] Of course, the present invention may have many other embodiments and variations thereof. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and variations based on the present invention, but these corresponding changes and variations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a polyglycolic acid catalyst, characterized in that: The following steps are involved: The amino acid and zinc acetate are dissolved in a solvent, and then heated, stirred, refluxed, and reacted in an oil bath. After the reaction is completed, the product is washed with a solution and dried to obtain a polyglycolic acid catalyst.

2. The method for preparing a polyglycolic acid catalyst according to claim 1, characterized in that: The molar ratio of the amino acid to zinc acetate is 1:0.5-2.

3. The method for preparing the polyglycolic acid catalyst according to claim 1, characterized in that: The amino acid is at least one of L-alanine, D-alanine, DL-alanine, L-phenylalanine, D-phenylalanine, DL-phenylalanine, L-proline, D-proline, DL-proline, L-threonine, D-threonine, DL-threonine, L-glutamic acid, D-glutamic acid, DL-glutamic acid, L-aspartic acid, D-aspartic acid, DL-aspartic acid, L-isoleucine, D-isoleucine, DL-isoleucine, L-leucine, D-leucine, DL-leucine, L-serine, D-serine, and DL-serine.

4. The method for preparing the polyglycolic acid catalyst according to claim 3, characterized in that: The amino acid is at least one of L-alanine, L-phenylalanine and L-proline.

5. The method for preparing the polyglycolic acid catalyst according to claim 1, characterized in that: The reaction temperature is 40-85°C and the reaction time is 2-8h.

6. The method for preparing the polyglycolic acid catalyst according to claim 5, characterized in that: The reaction temperature is 50-80°C and the reaction time is 3-6h.

7. The method for preparing a polyglycolic acid catalyst according to claim 1, characterized in that: The solvent is at least one of methanol, lauryl alcohol, dodecanol, anhydrous toluene and anhydrous ethyl acetate.

8. The method for preparing a polyglycolic acid catalyst according to claim 1, characterized in that: The method of using solution for rinsing is to repeatedly use ethanol and water as solvents for rinsing.

9. A polyglycolic acid catalyst, characterized in that The method is obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for adjusting polyglycolic acid molecular chain structure

    CN111647144A

  • Preparation method of polyglycolic acid

    CN112280021A

  • Preparation method of polyglycolic acid

    CN112831031A

  • Polymerization methods using the catalysts

    CN101291961A

  • Degradable poly(4-hydroxybutyrate) low-temperature 3D printing wire and preparation method thereof

    CN113150515A